From structured surveys to outbreak investigations: advancing genomic surveillance of carbapenem-resistant Enterobacterales within the European Antimicrobial Resistance Genes Surveillance Network - Kohlenberg, Anke; Linkevicius, Marius; Alm, Erik; Robesyn, Emmanuel; Svartström, Olov; Palm, Daniel; Monnet, Dominique L.; Plachouras, Diamantis; Albiger, Barbara (Frontiers in Public Health, 2025)
The European Antimicrobial Resistance Genes Surveillance Network (EURGen-Net) was established in 2017 to support the European survey of carbapenem- and/or colistin-resistant Enterobacterales in 37 countries. In parallel to large-scale international structured surveys with a central whole genome sequencing (WGS), EURGen-Net rapidly developed an approach for faster and more flexible investigations of cross-border outbreaks and emerging antimicrobial resistance of international concern in Europe, based on voluntary sharing of national WGS and epidemiological data for joint analysis. Here, we describe the approach and methodology, practical experience with implementation, benefits and challenges of the current model for genomic surveillance of carbapenem-resistant Enterobacterales at the European level.